PEMILIHAN BAHAN PEMULIAAN JAGUNG UNTUK PEMBENTUKAN VARIETAS UNGGUL DISKRIMINATIF TUMPANGSARI: PADI + JAGUNG + UBIKAYU DI LAHAN KERING.II. STABILITAS RELATIF BASIL BIJI PIPILAN KERlNG - Bari, Abdul; Sjamsudin, Endang; Subandi, , (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1998)
Intercropping of maize, rice and cassava is commonly practiced by subsistent farmers on rainfed agriculture in Indonesia. In general, grain yield (if maize in intercropping is lower than in monoculture sole crop. This due to the fact that maize varieties planted in intercropping was bred and selected under elite, monoculture crop environment. Field experiments to evaluate grain yield relative stability (if the three selected maize breeding materials planted in association with rice and cassava were carried out In Pekalongan (Lampung), December 1994 - September 1995. All three breeding materials are relatively stable in respect to grain yield. Individual selection in MC-1 population will be practiced in association with rice and cassava.